Efetivitas Restorative Justice dalam Penyelesaian Kasus Penyalahgunaan Narkotika di Indonesia - Riyansyah Riyansyah; Sintong Arion Hutapea (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Restorative justice is an alternative approach in the criminal justice system that focuses on restoring losses arising from criminal acts, as well as efforts for dialogue between perpetrators, victims, and the community. In the context of drug abuse in Indonesia, this approach is beginning to be considered as a more humane solution compared to conventional punishment, especially for addicts or users who are essentially victims of dependence. This study aims to analyze the effectiveness of the application of restorative justice in resolving drug abuse cases in Indonesia. The method used in this study is a juridical-normative approach with case studies and qualitative analysis of laws and regulations, law enforcement policies, and their implementation in the field. The results of the study indicate that although the concept of restorative justice has significant potential in encouraging rehabilitation and social reintegration for drug users, its implementation still faces various challenges, including the absence of clear regulations, community stigma, and resistance from some law enforcement officers. Therefore, it is necessary to strengthen regulations, training for officers, and public education to support the success of this approach in the drug criminal justice system in Indonesia.